Generalizable biomarker prediction from cancer pathology slides with self-supervised deep learning: a retrospective multi-centric study - Niehues, Jan Moritz; Quirke, Philip; West, Nicholas P.; Grabsch, Heike I.; van Treeck, Marko; Schirris, Yoni; Veldhuizen, Gregory P.; Hutchins, Gordon G. A.; Richman, Susan D.; Foersch, Sebastian; Brinker, Titus Josef; Fukuoka, Junya; et al. (Cell reports. Medicine, 2023)
Deep learning (DL) can predict microsatellite instability (MSI) from routine histopathology slides of colorectal cancer (CRC). However, it is unclear whether DL can also predict other biomarkers with high performance and whether DL predictions generalize to external patient populations. Here, we acquire CRC tissue samples from two large multi-centric studies. We systematically compare six different state-of-the-art DL architectures to predict biomarkers from pathology slides, including MSI and mutations in BRAF, KRAS, NRAS, and PIK3CA. Using a large external validation cohort to provide a realistic evaluation setting, we show that models using self-supervised, attention-based multiple-instance learning consistently outperform previous approaches while offering explainable visualizations of the indicative regions and morphologies. While the prediction of MSI and BRAF mutations reaches a clinical-grade performance, mutation prediction of PIK3CA, KRAS, and NRAS was clinically insufficient.